Fractured journeys : exploring possibilities of fractal verse : a thesis presented in partial fulfilment of the requirements for the degree of Master of Creative Writing, Massey University, Manawatu, New Zealand - Musters, Bridget Mary Auchmuty (Massey University, 2013)
In his book The Song of the Earth, Jonathan Bate acknowledges the question of the use of poetry in these highly technological times. If, as he asserts, ‘poetry is the place where we save the earth’, then the problem arises of how best to write poetry that addresses our most pressing concerns. Contemporary American poet Alice Fulton is one who does address social and political issues and has developed what she calls a ‘fractal’ poetic in order to do so. The research essay, titled ‘Fugue or/and Fugitive: Alice Fulton and the Poetics of Social Change’, examines how effective her poetics are as an agent of social change, and whether her work may serve as a useful model to move outwards from the personal concerns of an individual poet to a wider frame of public relevance. The first section of the essay looks at the social issues which Fulton raises in her poetry. These include human and animal rights, the politics of climate change, and deep-seated gender and racial inequities. Most of the poems examined come from her 1995 collection Sensual Math, because it is here that she introduces or employs some of her most characteristic techniques, such as an invented punctuation mark, word clusters, and syntactic doubling. Some of her more recent poems are also included in this context. The second section of the essay looks at Fulton’s theory of poetics and what other critics have said about it. It examines whether her techniques deliver on their promise to offer a non-didactic platform for activist poetry. The final section considers how I can apply Fulton’s techniques so that my own work moves beyond the merely solipsistic. My attempt to use fractal techniques is demonstrated in Unmooring, the poetry collection which constitutes the other half of this thesis. The first few poems are concerned with family history and the beginnings of an interface between poetry and eco-activism. Unexpected bereavement dictated both the form and the content of the central lyrical section. The collection concludes with poems which draw those elements together, applying a fractal poetic to personal engagement.
Keywords: Alice Fulton; Social change in poetry; Poetics; Poetry; Fractal verse